Time analysis for the IAAF World Championships London 2017 marathon men's - Hanley, B.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The men`s marathon took place on August 6th in the City of London. The race started and finished at Tower Bridge, with most of the distance covered using four loops of approximately 10 km each. The weather conditions were relatively mild with cloud cover at times. The lead men stayed together in a pack until roughly halfway. The race was won by Kirui, who bettered his winning time from Boston earlier in the year. The results for the first 32 finishers are shown.